How to send a finch extinct. Issue 94 (April 2019) - Reside, April E.; Cosgrove, Anita J.; Pointon, Revel; Trezise, James; Watson, James E.M.; Maron, Martine
Highlights: Environmental regulation failed to prevent habitat loss for an endangered species. Some habitat loss also occurred without government oversight. Regulatory processes approved over 400 developments without any conditions. Abstract: Australia's high species extinction rate shows no sign of abating, with at least three vertebrate extinctions recorded within the last decade. In each case, scientists have published 'post-mortems' examining the context of these recent extinctions. By tracing the decline of a once-widespread and common bird to the point that it has disappeared from over 80% of its original range, and describing the circumstances under which habitat loss continues to be approved despite its formal protection, we present a 'pre-mortem' for the endangered, and endemic, southern black-throated finch ( Poephila cincta cincta ). The southern black-throated finch has suffered extensive habitat loss historically, much of which was unregulated. In 2000, Australia increased environmental regulation, and the southern black-throated finch was listed under the Commonwealth's Environment Protection & Biodiversity Conservation Act. Despite the increased environmental regulation and formal protection, habitat loss for the southern black-throated finch has continued, mostly incrementally but resulting in large cumulative loss. In the face of steep population decline and range contraction of BTF, five large coal mines were approved between 2012 and 2015 by both State and Commonwealth governments that will remove most of the largest area of high quality habitat that remains. We outline the policy settings under which the decline occurred, with a particular focus on recent ongoing habitat loss occurring within a highly regulated environment. We show that despite Australia's comparatively strong governance and regulatory frameworks, legally permitted habitat loss continues even for imperilled taxa formally listed under State and Commonwealth environment protection laws.